The emergence and current performance of a health research system: lessons from Guinea Bissau - Kok Maarten O; Rodrigues Amabelia; Silva Augusto; de Haan Sylvia (BMC, 2012)
Abstract Background Little is known about how health research systems (HRS) in low-income countries emerge and evolve over time, and how this process relates to their performance. Understanding how HRSs emerge is important for the development of well functioning National Health Research Systems (NHRS). The aim of this study was to assess how the HRS in Guinea Bissau has emerged and evolved over time and how the present system functions. Methods We used a qualitative case-study methodology to explore the emergence and current performance of the HRS, using the NHRS framework. We reviewed documents and carried out 39 in-depth interviews, ranging from health research to policy and practice stakeholders. Using an iterative approach, we undertook a thematic analysis of the data. Results The research practices in Guinea Bissau led to the emergence of a HRS with both local and international links and strong dependencies on international partners and donors. The post-colonial, volatile and resource-dependent context, changes in donor policies, training of local researchers and nature of the research findings influenced how the HRS evolved. Research priorities have mostly been set by 'expatriate' researchers and focused on understanding and reducing child mortality. Research funding is almost exclusively provided by foreign donors and international agencies. The training of Guinean researchers started in the mid-nineties and has since reinforced the links with the health system, broadened the research agenda and enhanced local use of research. While some studies have made an important contribution to global health, the use of research within Guinea Bissau has been constrained by the weak and donor dependent health system, volatile government, top-down policies of international agencies, and the controversial nature of some of the research findings. Conclusions In Guinea Bissau a de facto 'system' of research has emerged through research practices and co-evolving national and international research and development dynamics. If the aim of research is to contribute to local decision making, it is essential to modulate the emerged system by setting national research priorities, aligning funding, building national research capacity and linking research to decision making processes. Donors and international agencies can contribute to this process by coordinating their efforts and aligning to national priorities.